Формулы сумм и разностей куба таковы:
(a + b)³ = a³ + 3a²b + 3ab² + b³
(a - b)³ = a³ - 3a²b + 3ab² - b³
А в примерах два слагаемых надо представить как “a” и “b”.
(a + 2x)³ = a³ + 6a²x + 12ax² + 8x³
(4n - 3m)³ = 64n³ - 144n²m + 108m²n - 27m³
(-c - 3k)³ = -c³ - 6c²k - 27ck² + 27k³
решение смотри на фотографии
Формулы сумм и разностей куба таковы:
(a + b)³ = a³ + 3a²b + 3ab² + b³
(a - b)³ = a³ - 3a²b + 3ab² - b³
А в примерах два слагаемых надо представить как “a” и “b”.
(a + 2x)³ = a³ + 6a²x + 12ax² + 8x³
(4n - 3m)³ = 64n³ - 144n²m + 108m²n - 27m³
(-c - 3k)³ = -c³ - 6c²k - 27ck² + 27k³
решение смотри на фотографии